1996
DOI: 10.1111/j.1469-8137.1996.tb04361.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses to water stress in an ABA ‐ unresponsive hybrid poplar (Populus koreana×trichocarpa cv. Peace) I. Stomatal function

Abstract: SUMMARY The poplar cultivar ‘Peace’ (Populus trichocarpa×koreana) displays abnormal stomatal behaviour with a lack of sensitivity to exogenous abscisic acid (ABA) in mature leaves. We report details of the leaf‐age dependency of this feature, and present the responses of stomata to diverse closing stimuli in addition to ABA. Soil water depletion induced complete stomatal closure of the youngest leaves, whereas the oldest exhibited almost no closure. By contrast, no such age effect was observed in stomatal sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 48 publications
(52 reference statements)
1
17
0
Order By: Relevance
“…This difference might be at least partly due to the fact that leaves of ' Peace' present a very small stomatal density on the adaxial surface, whereas both cultivars display similar densities on the abaxial side. In ' Peace ', conductance of the adaxial side represented c. 10% of the leaf conductance, whereas in 'Robusta' it was c. 40% (Ridolfi et al, 1996). Likewise, CO2 assimilation rates {A) were c. 12-7+ 0-93 //mol m"^ s'^ in leaves of ' Robusta' and only 9-9 + 0-9 in ' Peace' (P = 0-0002).…”
Section: Leaf Gas Exchangementioning
confidence: 96%
See 3 more Smart Citations
“…This difference might be at least partly due to the fact that leaves of ' Peace' present a very small stomatal density on the adaxial surface, whereas both cultivars display similar densities on the abaxial side. In ' Peace ', conductance of the adaxial side represented c. 10% of the leaf conductance, whereas in 'Robusta' it was c. 40% (Ridolfi et al, 1996). Likewise, CO2 assimilation rates {A) were c. 12-7+ 0-93 //mol m"^ s'^ in leaves of ' Robusta' and only 9-9 + 0-9 in ' Peace' (P = 0-0002).…”
Section: Leaf Gas Exchangementioning
confidence: 96%
“…A lower leaf stomatal conductance to CO2 (g,,) was observed in ' Peace' during the experiment at moderate irradiance, but not during the second, under low irradiance. A lower conductance can be partly explained by the low stomatal density on the adaxial leaf side, which contributes to only 10 °o of ^^ in 'Peace' vs. 40% in 'Robusta' (Ridolfi et al, 1996). Reich (1984) showed that the difterences in leaf conductance between three hybrid poplars were related to their respective stomatal densities.…”
Section: I S C Li S S 1 O Nmentioning
confidence: 99%
See 2 more Smart Citations
“…Peace) has stomata unresponsive to exogenous abscisic acid (Furukawa, Park & Fujinuma, 1990), a plant growth regulator supposed to be one of the major molecules triggering stomatal closure in response to soil water deficit. Ridolfi et al (1996), working on the same hybrid, complemented the first observation of Furukawa et al (1990) by demonstrating a leaf-age dependency of stomatal response to drought for this hybrid: the youngest apical leaves exhibit stomatal regulation but partly lose this capacity when they mature. Correlatively, droughted cuttings rapidly shed their mature leaves while the youngest ones survive the drought.…”
Section: Introductionmentioning
confidence: 99%